Leptin ve periodontal hastalıklar - Tugba Aydin; Meltem Zihni; Alparslan Dilsiz (Cumhuriyet University, 2011)
Leptin, a hormone secreted by adipose tissue, but also by several other tissues, and it plays an important role in protection of the host from inflammation and infection. Periodontal diseases are multi-factorial infectious disorders that lead to destruction of the supporting tissues of the teeth. These diseases are the result of bacterial infections of the gingival tissues. Therapy to decrease the levels of oral microorganisms can reduce gingivitis and stabilize periodontitis. Previous studies have suggested a relationship between periodontal disease and leptin levels. Some researchers reported that there is a strong negative correlation between the gingival crevicular fluid (GCF) leptin level and periodontal disease progression, after the presence of leptin within healthy and inflamed gingiva has been demonstrated. The aim of this paper is to summarize the effect of leptin in the human body and to report relationship between periodontal disease and leptin levels. ÖZET Leptin, konağı inflamasyon ve infeksiyondan koruyucu önemli bir rolü olan, yağ dokusundan başka ilave çeşitli dokulardan da salgılanan bir hormondur. Periodontal hastalıklar, dişlerin destek dokularının yıkımına yol açan birden fazla faktörün sebep olduğu infeksiyöz hastalıklardır. Bu hastalıklar gingival dokularda bakteriyel infeksiyonlar sonucu oluşurlar. Oral mikroorganizmaların seviyelerini azaltarak yapılan tedavi, gingivitisi engelleyebildiği gibi, periodontitisi de stabilize edebilir. Daha önceleri yapılan çalışmalar da leptin seviyeleri ile periodontal hastalıklar arasında bir ilişki olduğunu ileri sürmüşlerdir. Bazı araştırıclar, sağlıklı ve hastalıklı gingivada leptinin varlığı gösterildikten sonra dişeti oluğu sıvısı leptin seviyesi ile periodontal hastalığın şiddeti arasında güçlü bir negatif korelasyon olduğunu bildirmişlerdir. Bu derlemenin amacı, leptin seviyeleri ve periodontal hastalık arasındaki ilişkiyi bildirmek ve insan vücuduna leptinin etkilerini özetlemektir. Anahtar Kelimeler; Hormon, leptin, periodontal hastalık, dişeti, dişeti iltihab ve dişeti oluğu sıvısı